Dissociation of left ventricular hypertrophy, β-Myosin Heavy Chain gene expression, and myosin isoform switch in rats after ascending aortic stenosis - Wiesner, Rudolf J.; Ehmke, Heimo; Faulhaber, Jörg; Zak, Radovan; Rüegg, Johann Caspar (Circulation, 1997)
Background Reexpression of the fetal β-myosin heavy chain (β-MHC) gene was reported to be a marker for phenotypic reprogramming and cardiac hypertrophy in rats. Recent in vitro studies strongly suggested a role of angiotensin II for phenotypic reprogramming. In the present investigation, β-MHC gene expression was studied in an experimental model of pressure-overload hypertrophy that is not associated with a concurrent activation of the circulating renin-angiotensin system. - Methods and Results Hypertrophy was induced in rats by ascending aortic banding (n=40). After 7 days, myosin contained 31% (P<.05) of the β-MHC isoform in banded but <5% in sham-operated animals. However, no specific elevation of β-MHC mRNA levels was found in banded animals. In contrast, hearts of rats with abdominal aortic banding displayed a marked increase in β-MHC mRNA levels (3-fold to 5-fold, P<.05). Both the left ventricular weight and left ventricular peak systolic pressure were significantly elevated compared with sham-operated animals (abdominal aortic banding, +13% and 164±7 mm Hg; ascending aortic banding, +27% and 191±9 mm Hg). Plasma renin activity was elevated in rats with abdominal aortic banding (2.5-fold, P<.05) but not in rats with ascending aortic banding. - Conclusions The results of the present work do not support the concept that increased β-MHC gene expression is a general “stable late marker” of myocardial hypertrophy in rats. Our results suggest that the stimulation of the renin-angiotensin system is crucial for the activation of the β-MHC gene.